Synthesis And Characterisation Of New Dispiro Pyrrolidines As Cholinesterase Inhibitors - Mohamed Yusoff, Nadia (2019)
Spiro compounds are widely known for their diverse biological activities and become an important target by researchers to study and to produce synthetically. Alzheimer’s disease known as a neurodegenerative disorder with its number of cases reported increases every year worldwide. With available treatments that are only able to slow down the symptoms, there is an urgent need to continue developing more efficient drugs in targeting the cholinesterase enzymes activities inhibition. In this study, three dienones derivatives, 3,5-bis(arylidene)-1-phenylethyl-4-piperidone (19-21) and fifteen new spiro heterocycles are known as dispiro pyrrolidines (22-24) were successfully synthesised afforded in good yield with a range of 85.4-94.6 and 81.3-98.1 %, respectively.